PENGARUH KECERDASAN EMOSIONAL DAN KEPERCAYAAN DIRI TERHADAP KINERJA KARYAWAN PADA PT WINGS SURYA CABANG SEMARAPURA - Rita Hirthindy Maya; I Wayan Mendra; I Gst Ngr Bagus Gunadi; I Wayan Cipta; I Dewa Made Adnyana (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2018)
Employees are the company’s assets that determine success in achieving its objectives. In obtaining a good performance of the company should provide Emotional Quotient and Confidence that serves to enhance the employee performance. The research was conducted on employees of PT Wings Surya Semarapura Branch. The phenomenon that occurs is the resulting performance of the employee has been unable to meet the specified performance targets management of PT Wings Surya Semarapura Branch. The method used in this study is qualitative and quantitative methods. The unit of analysis in this study is a combined workforce of about 39 employees. The test statistic used is regression analysis, correlation, hypothesis testing.The results of the analysis explain thatEmotional Quotient and Confidence simultaneously have a positive and significant impact on employee performance. And based on t test results, Emotional Quotient and Confidence variables have a positive and significant influence on employee performanceofPT Wings Surya Semarapura Branch.